EVALUASI PEMILIHAN SUPPLIER SAYUR PADA PT DWI TUNGGAL CITRA CATERING DENGAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) DAN BEST WORST METHOD (BWM) - Muhammad Raihan Zuchriadi Putra (2023)
One type of business in the culinary sector that is quite popular at the moment is the catering business. With the large number of catering businesses in Indonesia, in order to be competitive, companies need to improve their performance. There are various factors that influence company performance, one of which is the company's selection of suppliers. The supplier selection process is a very crucial stage for companies to increase supply chain efficiency and obtain high-quality products. PT Dwi Tunggal Citra Catering is a company that focuses on the catering industry, which relies heavily on selecting effective and efficient suppliers. The problem with relationships with suppliers is that not all of them can meet all the criteria set by the company. Due to the lack of optimal supplier determination factors, research is needed to evaluate the selection of the best supplier for the vegetable procurement process at PT Dwi Tunggal Citra Catering. Suppliers who are suitable are expected to be able to minimize the possibility of losses and help smooth the movement of supplies in the supply chain by implementing the Analytical Hierarchy Process (AHP) and Best Worst Method (BWM) methods. Based on the results of data processing that the author has carried out using the AHP method, the criteria assessment weights are obtained from the highest level of importance to the lowest level of importance, namely quality of 0.33, delivery of 0.29, flexibility of 0.19, responsiveness of 0.11, and a fee of 0.08. The results of processing criteria data using the BWM method and processing supplier data using the AHP method show that the supplier with the highest optimal weight is Supplier C, which has an optimal weight of 0.9 and is the supplier with the most potential and meets the criteria. Meanwhile, Supplier B is in second place with an optimal weight of 0.07, and Supplier A gets an optimal weight of 0. So it can be concluded that the one who can be used as a priority supplier for further collaboration in the vegetable procurement process at PT Dwi Tunggal Citra Catering is supplier C.